Revealing the non-Muslim Kopitiams and the awarded Halal Signage - Embong, A.M. (Medwell Journals, 2018)
The growth of Kopitiam is mushrooming as it provides simple yet, fast meals in accordance to the vibrant lifestyle of today's society. As the financial commitment to operate the Kopitiam is high compared to ordinary restaurants or other eating outlets, most are dominated by the non-Muslims who venture the Kopitiam business to cater the needs of the muslim customers. The signage of Halal is then becoming the focus point among the Muslims. This study is about the understanding and practice of non-Muslim Kopitiam operators regarding Halal signage in one densely populated town in Terengganu. The study involves stakeholders of the thence Kopitiams. The study is qualitative in nature, involving six non-Muslim Kopitiam operators in interview sessions. The findings reveal that the operators have good understanding and practice of running Kopitiams regarding the Halal signage awarded to them. All non-Muslim operators understand the concept of Halal to be applied in their Kopitiams. The practice is fully utilised because the respondents run their business within Muslim-Malay population. Besides, the operators hire Muslim workers and the cooking activity for the Kopitiam is solely done at the Kopitiam itself. Â© Medwell Journals, 2018.